2021
DOI: 10.52547/ijn.34.129.67
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Self-care Status in Older Adults Diagnosed with Heart Failure and Hospitalized in the Cardiovascular Intensive Care Units of the Public Hospitals in the East of Guilan, Iran (2020)

Abstract: Background & Aims: One of the most common diseases during old age is cardiovascular disease. Heart failure is the leading cause of death, disease, hospitalization, and poor quality of life. There are different approaches for controlling heart failure, including self-care, and adherence to self-care behaviors in patients suffering from this disease is very important. People with effective self-care have a better quality of life, and mortality and readmission rates are lower among these people than those with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Nevertheless, another study found employed elderlies have reported fewer symptoms of depression by 1.72 units compared with unemployed elderlies 37 . The prevalence of depression in elderly suffering from HTN had no significant relationship with comorbidity 27,44 ; however, in other studies, there was a significant relationship between prevalence of depression and comorbidity 36,45 . Similar studies have shown a significant relationship between the constant need for care and prevalence of depression among the elderly 4,46–48 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, another study found employed elderlies have reported fewer symptoms of depression by 1.72 units compared with unemployed elderlies 37 . The prevalence of depression in elderly suffering from HTN had no significant relationship with comorbidity 27,44 ; however, in other studies, there was a significant relationship between prevalence of depression and comorbidity 36,45 . Similar studies have shown a significant relationship between the constant need for care and prevalence of depression among the elderly 4,46–48 .…”
Section: Discussionmentioning
confidence: 79%
“…37 The prevalence of depression in elderly suffering from HTN had no significant relationship with comorbidity 27,44 ; however, in other studies, there was a significant relationship between prevalence of depression and comorbidity. 36,45 Similar studies have shown a significant relationship between the constant need for care and prevalence of depression among the elderly. 4,[46][47][48] It seems that personal and social differences of the elderly across different countries and even the cities of one country with varying cultures and attitudes would affect the extent of their distress considering their special conditions.…”
Section: Discussionmentioning
confidence: 81%